Law and politics of religious fraud regulation: China, Taiwan and Hong Kong - Chen, Jianlin (Elgar studies in law and society, 2023)
"In comparing the ways in which China, Taiwan and Hong Kong punish religious claims and practices considered by the state to be false or fraudulent, Jianlin Chen presents a seminal contribution to the interdisciplinary study of religious freedom. The book not only reveals how these legal tools sustain a hierarchy of religion, but also the political dynamic behind the design and utilization of these legal tools. Adopting a novel, comparative approach, Chen adeptly investigates various legal tools employed to regulate religious fraud in China, Taiwan and Hong Kong. Through a systematic survey of court judgments, he identifies the surprising convergences among the religious fraud regulations across the three jurisdictions. He further employs public choice analysis to tease out the reasons behind these often unconstitutional religious fraud regulations, and highlights the complicity of individuals who otherwise advocate for liberal democratic values. With its wealth of legal and political analysis, the book critically interjects in the global inquiry of religious freedom and democratic backsliding. This progressive book is an important touchstone for scholars and students in Asian studies, law and religion, criminal law and justice, and law and society"--